2002
DOI: 10.1097/00007890-200211150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Smooth-muscle progenitor cells of bone marrow origin contribute to the development of neointimal thickenings in rat aortic allografts and injured rat carotid arteries1

Abstract: This study indicates that circulating progenitors of bone marrow origin give rise to cells with smooth muscle-like properties during formation of neointimal thickenings in the arterial wall after allotransplantation and after balloon injury. A segment of abdominal aorta was transplanted from female F344 to male LEW rats, and the grafts were analyzed for male cells by using the gene as a marker. Immunostaining demonstrated that CD45-positive leukocytes made up 35-45% of the neointimal cells during the 8-week pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…The existence of stem cells in the fistula wall was recently suggested by Caplice et al (8), who described this type of cells as components of adventitial microvessels in the rat A-V fistula. A number of studies have proposed bone marrow-derived progenitor cells as the source of neointimal cells in stenotic blood vessels after arterial injury (38,44,46), but their contribution seems less pronounced in the case of venous hyperplasia, as clearly demonstrated in three independent studies (9,21,43). The present work highlights the critical role played by this pathway in A-V fistula remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…The existence of stem cells in the fistula wall was recently suggested by Caplice et al (8), who described this type of cells as components of adventitial microvessels in the rat A-V fistula. A number of studies have proposed bone marrow-derived progenitor cells as the source of neointimal cells in stenotic blood vessels after arterial injury (38,44,46), but their contribution seems less pronounced in the case of venous hyperplasia, as clearly demonstrated in three independent studies (9,21,43). The present work highlights the critical role played by this pathway in A-V fistula remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…In vitro, marrow stromal cells have been shown to differentiate into bone, fat, cartilage, neuron, or muscle when treated with specialized induction media. Recent studies have indicated that smooth muscle-like cells also can be derived from bone marrow cells both in vitro (17,18) or in vivo (3,5). However, bone marrow is not the only site of adult stem cells capable of multiple differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have suggested the use of bone marrow-derived cells (3)(4)(5) and embryonic stem cells to repair smooth muscle tissues (6,7) because of their stem cell-like properties. Adipose tissue represents a potential alternative reservoir of cells with stem cell properties such as self-renewal and pluripotency.…”
mentioning
confidence: 99%
“…Application of a blocking SDF-1␣ mAb reduces neointimal area and neointimal SMC content, which indicates an important role during the progression of accelerated atherosclerosis. Because SDF-1␣ is important in the homeostasis of bone marrow homing and mobilization of progenitor cells, 7,19 and neointimal SMCs originate from a bone marrow source of progenitors, [13][14][15] we studied the effect of SDF-1␣ on progenitor cell mobilization and recruitment after carotid injury. We found that the expansion of PBPCs in the circulation and the accumulation of injected PBPCs in established neointimal lesions were mediated by SDF-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neutralization of SDF-1␣ after carotid injury in apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mice by application of a blocking antibody was evaluated for its effect on neointimal lesions. Bone marrowderived cells have been shown to contribute to neointimal SMC content, [13][14][15] and circulating SMC progenitors have been demonstrated in humans. 16 We therefore determined whether SDF-1␣ is involved in the mobilization of progenitor cells into the peripheral blood and whether these cells can be recruited to neointimal lesions and adopt an SMC phenotype.…”
mentioning
confidence: 99%